Diet and lifestyle of the Sami of southern Lapland in the 1930s-1950s and today - Nilsson, Lena M.; Dahlgren, Lars; Johansson, Ingegerd; Brustad, Magritt; Sjolander, Per; Van Guelpen, Bethany (University of Oulu, 2011)
To describe the lifestyle of the Sami of southern Lapland 50 to 70 years ago in relation to the present-day Sami and non-Sami populations and, thereby, to provide a basis for future studies of culturally related determinants of health and illness. A qualitative analysis, and a quantitative comparison of Sami and non-Sami groups. Semi-structured interviews were conducted with 20 elderly Sami concerning their parents’ lifestyle and diet 50 to 70 years ago. Questionnaire data from 81 reindeer-herding Sami, 226 non-reindeer-herding Sami and 1,842 sex-, age- and geographically matched non-Sami from the population-based Västerbotten Intervention Project were analysed by non-parametric tests and partial least squares methodology. Surprisingly, fatty fish may have been more important than reindeer meat for the Sami of southern Lapland in the 1930s to 1950s, and it is still consumed more frequently by reindeer-herding Sami than nonreindeer-herding Sami and non-Sami. Other dietary characteristics of the historical Sami and present-day reindeer-herding Sami were higher intakes of fat, blood and boiled coffee, and lower intakes of bread, fibre and cultivated vegetables, compared with present-day non-Sami. Physical activity was also a part of the daily life of the Sami to a greater extent in the 1930s to 1950s than today. Sami men often worked far from home, while the women were responsible for fishing, farming, gardening (which was introduced in the 1930–1950 period), as well as housework and childcare. For studies investigating characteristic lifestyle elements of specific ethnic groups, the elements of greatest acknowledged cultural importance today (in this case reindeer meat) may not be of the most objective importance traditionally.